KANDUNGAN BISPHENOL A (BPA) PADA KEMASAN BERBAHAN DASAR PLASTIK PERSPEKTIF UU PERLINDUNGAN KONSUMEN DAN MASLAHAH MURSALAH - Qolbi, Wasiatul (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Â The packaging sector is an important industry. One of the packaging materials that is often used is plastic packaging. In plastic packaging there is one of the BPA materials used in the manufacturing process. This BPA content has the potential to be released and mixed with packaged foods and beverages. While BPA is a content that can cause various diseases such as cancer. This study aims to determine the content of BPA in plastic packaging seen from the Consumer Protection Act and Maslahah Mursalah. This study uses normative legal research that is descriptive analytical with a qualitative approach to primary data, secondary data and tertiary data which includes the content and structure of positive law. The results showed that the BPA content in plastic packaging did not comply with several articles in the Consumer Protection Act. It is stated that one of the rights of consumers is to get a sense of security and safety in consuming goods and services. The content of BPA which can cause various diseases is clearly not in accordance with the clauses in the Consumer Protection Act. In maslahah mursalah, the discovery of the use of plastic as food and beverage packaging can be said to be useful, it can also be said to be useless. Plastic packaging can be said to be useful if the plastic packaging is in accordance with its purpose, namely to protect food and beverages from external contamination. The presence of Bhispenol A in the plastic base material causes losses